Gully erosion processes, disciplinary fragmentation, and technological innovation. Issue 1 (31st October 2018) - Bennett, Sean J.; Wells, Robert R.
Abstract: The development and evolution of gullies on soil‐mantled hillslopes can devastate agricultural regions and cause widespread soil and landscape degradation. Since 2000, international symposia have been organized to address gully erosion processes, and this paper and special issue provide additional context for the 7th International Symposium on Gully Erosion held at Purdue University in 2016. Several important themes of gully erosion emerged during this symposium that warranted additional discussion here. These topics include the importance and impact of technology transfer, disciplinary fragmentation as an impediment for research advancement, the difficulty in defining the erodibility of sediment within gullies, and the opportunities afforded by remote sensing technology. It is envisioned that such symposia will continue to enhance the capabilities of researchers and practitioners to monitor, model, and manage these important geomorphic processes and to mitigate landscape degradation. © 2018 John Wiley & Sons, Ltd. Abstract : Gully erosion is a global driver of soil and landscape degradation. Since 2000, international symposia have been organized to address gully erosion processes, and this paper and special issue provide additional context for the 7 th International Symposium on Gully Erosion held at Purdue University in 2016. Several important themes emerged that include the importance and impact of technology transfer, disciplinary fragmentation as an impediment for research advancement, the difficulty in defining the erodibility of sediment within gullies, and the opportunities afforded by remote sensing technology.